Interpretation von ökologischen Karten am Beispiel des Ätna - Werner, Dietrich J. (ERDKUNDE, 1973)
In this paper maps of the small regional units (morphoecological units and ecotopes) of the upper parts of Mount Etna will be interpreted. Short descriptions of all units are given in advance. Degree of covering and frequency of the units in the mapped area are used as criteria for the ecological description and interpretation. Also arrangement, shape and size of the units and the location of the units in relation to others or in relation to the relief allow definite ecological statements. An interpretation like the one suggested only fragmentarily and in the form of a model in this study, is a good method to confirm the statements of field-research and to gain new complementary results.